Technical and economic analysis of different coffee (Coffea arabica L.) transplanting system - Cunha, João Paulo Barreto; da Silva, Fabio Moreira; Andrade, Fabricio; Machado, Tulio de Almeida; Batista, Francinaldo Alves (Coffee Science - ISSN 1984-3909, 2015)
Coffee is a prominent crop in Brazil, so much that in recent years, coffee crop has undergone major changes such as the introduction of mechanization in different operations previously performed manually, and if the transplant operation using machinery has become an viable alternative for farmers enabling increased operational capacity. The trial was carried out in Nazareno- MG, aiming to conduct a technical and economic analysis of different systems of transplanting. This work was carried out employing mechanized assembly used for the realization of transplanting of cultivar Catuaí IAC 144. The time required to perform various operations in different sets of mechanized systems evaluated and their fixed and variable costs, and determined the operating performance were analyzed. Based on the results obtained, the system of mechanized transplanting showed higher technical and economic viability in relation to others. The depreciation, repairs and maintenance and fuel consumption are the components of costs that most affect the operating cost occurs in systems where use of machinery with greater intensity.